PREDICTIVE VALUE OF TYMPANIC MEMBRANE INJURY IN DETERMINING MORTALITY/MORBIDITY ASSOCIATED WITH TERRORIST BOMB BLASTS - Raza, Sayed Nusrat; Ahmed, Shakeel; Raahat, ZM; Haider, Irfan Zafar; Ali, Muhammad; Waleem, Sheikh Saadat Ullah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To analyze the predictive value of drumhead perforation to overall visceral damage by the blast waves.Study Design: Retrospective observational study.Place and Duration of Study: It was a multi-centric study extending from Jul 2005 to Jun 2009. Blast victims in Wana (Pak Afghan border area, a hot center of war against terrorism in Pakistan), Lahore (provincial capital of Punjab, Pakistan) and Quetta (provincial capital of Baluchistan, Pakistan) were included in the study.Methodology: A total of 354 patients were included in the study. A preliminary examination by surgeon and ENT specialist was carried out to evaluate patient’s general condition and state of tympanic membranes. Sonographic examination, computerized tomography (CT) scan and other relevant investigations were subsequently carried out to further ascertain the patient’s condition and visceral damage. The data were then analyzed to correlate visceral damage as a result of blast injury to the laterality and size of tympanic membrane perforation.Results: The extent of visceral damage was less in cases with intact drumheads, more in cases with unilateral perforation and maximum in cases with bilateral subtotal perforation.Conclusion: The size and laterality of drumhead perforation as a result of blast injury is a rough predictor of visceral damage sustained as a result of blast injury.